EVALUATION OF RISK FACTORS LEADING TO ROP IN SOUTHERN PUNJAB, A HOSPITAL BASED STUDY - MALIK , A; ASIF , M; HASSAN , F; RAO , MRQ; AADIL , N (Biological and Clinical Sciences Research Journal, 2023)
The study aimed to assess the risk factors associated with retinopathy of prematurity (ROP) in premature children. The study was conducted prospectively in the Neonatal Unit of Nishtar Medical Hospital from January 2022 to December 2022 located in southern Punjab. The study included premature children who had a birth weight of less than 1500 g, gestational age of 32 weeks or less, and infants who had low Apgar scores, respiratory distress syndrome, blood transfusion, sepsis, infection, hydrocephaly, microcephaly, and twin pregnancy. Children with ischemic zones and changes in blood vessels had ROP and were treated by ophthalmologists and surgeons. The study found that out of the total 70 premature children included, 4 (5.7%) had active ROP, and 66 (94.2%) showed spontaneous regression of ROP. The patients with active ROP had a mean gestational age of 27.4±1.4 weeks, and there was a significant association between early gestational age and ROP. Patients who developed active ROP had oxygen therapy for 21±3.5 days compared to 12.6±1.2 days in those without ROP (P<0.05). The most common retinal changes were the development of ischemic zones (61.4%), bleeding (24.2%), changes in blood vessels (15.7%), and changes in the optic nerve (1.4%). Of the 70 patients, 4 (5.7%) were in Zone I, 21 (30%) were in Zone II, and 45 (64.2%) were in Zone III. All patients in the zone I had active ROP, suggesting a significant association between zones and the development of ROP (P <.05). In conclusion, the study found that low birth weight, early gestational age, low Apgar score, and longer duration of oxygen therapy significantly increased the risk of ROP.